Rand McNally children's atlas of the environment. - Rand McNally and Company; Rand McNally and Company (Chicago : Rand McNally, 1991)
Maps and text portray the world's ecosystems, and environmental concerns, and includes positive suggestions of what can be done to help the planet.
Includes indexes and glossary.
Appraisal-Science Books for Young People.
Wilson's Junior High School.
5.9
5.9
3-6.
Keywords: Environmental protection -- Maps; Human ecology -- Maps; Man -- Influence on nature -- Maps; Environmental protection -- Maps; Human ecology -- Maps; Man -- Influence on nature -- Maps; Environmental protection -- Maps; Human ecology -- Maps; Human influence on nature -- Maps